CAR-T Plus Radiotherapy: A Promising Combination for Immunosuppressive Tumors - Qin, Vicky Mengfei; Haynes, Nicole M.; D’Souza, Criselle; Neeson, Paul J.; Zhu, Joe Jiang (Frontiers in Immunology, 2022)
Radiotherapy (RT) is the standard-of-care treatment for more than half of cancer patients with localized tumors and is also used as palliative care to facilitate symptom relief in metastatic cancers. In addition, RT can alter the immunosuppressive tumor microenvironment (TME) of solid tumors to augment the anti-tumor immune response of immune checkpoint blockade (ICB). The rationale of this combination therapy can also be extended to other forms of immunotherapy, such as chimeric antigen receptor T cell (CAR-T) therapy. Similar to ICB, the efficacy of CAR-T therapy is also significantly impacted by the immunosuppressive TME, leading to compromised T cell function and/or insufficient T cell infiltration. In this review, we will discuss some of the key barriers to the activity of CAR-T cells in the immunosuppressive TME and focus on how RT can be used to eliminate or bypass these barriers. We will present the challenges to achieving success with this therapeutic partnership. Looking forward, we will also provide strategies currently being investigated to ensure the success of this combination strategy in the clinic.